Global trends in tumor-associated neutrophil research: a bibliometric and visual analysis - Li, Shaodong; Dong, Peng; Wu, Xueliang; Kang, Zhenhua; Yan, Guoqiang (Frontiers in Immunology, 2025)
BackgroundTumor-associated neutrophils (TANs) play crucial roles in tumor progression, immune response modulation, and the therapeutic outcomes. Despite significant advancements in TAN research, a comprehensive bibliometric analysis that objectively presents the current status and trends in this field is lacking. This study aims to fill this gap by visually analyzing global trends in TANs research using bibliometric and knowledge mapping techniques.MethodsWe retrieved articles and reviews related to TANs from the Web of Science core collection database, spanning the period from 2012 to2024. The data was analyzed using bibliometric tools such as Excel 365, CiteSpace, VOSviewer, and Bibliometrix (R-Tool of R-Studio) to identify key trends, influential countries and institutions, collaborative networks. and citation patterns.ResultsA total of 6l5 publications were included in the bibliometric analysis, showing a significant upward trend in TANs research over the last two decades. The United States and China emerged as the leading contributors with the highest number of publications and citations. The journal with the most publications in this field is Frontiers in Immunology, Prominent authors such as Fridlender ZG was identified as the key contributor, with his works frequently cited. The analysis highlighted major research themes. including the role of TANs in tumor microenvironment modulation, their dual functions in tumor promotion and suppression, and the exploration of TANs-targeted therapies, Emerging research hotspots include studies on TANs plasticity and their interactions with other immune cells.ConclusionThis study is the first to employ bibliometric methods to visualize trends and frontiers in TANs research. The findings provide valuable insights into the evolution of the field, highlighting critical areas for future investigation and potential collaborative opportunities. This comprehensive analysis serves as a crucial resource for researchers and practitioners aiming to advance TAN research and its application in cancer therapy.